MILLENNIAL MOVEMENT IN ANGIE THOMAS’ THE HATE U GIVE - Jeksen Fillan Nani; Olga A. Rorintulus; Jennie Posumah (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2023)
This study aims to uncover the involvement of millennials in the Black Lives Matter movement, which is also called The Millennial Movement against racial discrimination in Angie Thomas' novel, The Hate U Give. The researcher uses qualitative methods. The data are presented descriptively. The mimetic approach is used in this study to help the researcher examine the representation of the movement in the novel and its relationship with real-world movement. The results of the study indicate that millennials play an important role in the movement by participating in various forms of activities such as demonstrations, social actions, and social media to fight against social inequality, injustice, and discrimination towards Khalil and the black community. The implications of the research on the novel emphasize the importance of the younger generation in speaking up for justice in society. The novel encourages the younger generation to be courageous and use their voices to advocate for a more equitable and inclusive world. It teaches us that positive change can happen when we all work together, and that the younger generation can play a pivotal role in shaping a better future for us all.